URBAN TRAFFIC MANAGEMENT SYSTEM BY CCTV MONITORING - CLAUDIA SARA, SENIN (Universiti Malaysia Sarawak (UNIMAS), 2018)
The growth of human population in urban cities causes a hike in vehicle density.The growth of human population in urban cities causes a hike in vehicle density. Therefore, traffic control system plays a significant role in alleviating the traffic congestion. The traffic control system provides safety and ease to both drivers and also pedestrians. Nonetheless, the usability of accustomed traffic control signals fails in terms of time management and flow control to the road users. This creates irrelevant waiting time for the drivers. This project proposes the application of Indigo Vision Closed-Circuit Television (CCTV) camera provided by Kiwitech Sdn. Bhd as a monitoring-based traffic management system to overcome the problem of traffic control system in terms of flow and time management. The CCTV will be used as an input sensor that provides a real-time traffic data. Arduino board, Ethernet shield (Wiznet 5100) and LEDs (Light Emitting Diode) are used to setup the prototype system. It is use to demonstrate the T-junction added with green light delay interval time. The delay time will be programmed by using C++ programming language which will be compiled through Arduino IDE software. The Ethernet shield will act as the sender of the traffic data. The data will be transmitted to the server which will be done by CIDTS Unimas (Centre for Information Development and Services). Mobile application used by user will received the information provided by the server. The proposed project will improve the time management for road user to reach their destination. It can be further used on a larger scale in real time for better and safer road using Mobotix IP (Internet Protocol) camera that can analyse the traffic count automatically. Therefore, traffic control system plays a significant role in alleviating the traffic congestion. The traffic control system provides safety and ease to both drivers and also pedestrians. Nonetheless, the usability of accustomed traffic control signals fails in terms of time management and flow control to the road users. This creates irrelevant waiting time for the drivers. This project proposes the application of Indigo Vision Closed-Circuit Television (CCTV) camera provided by Kiwitech Sdn. Bhd as a monitoring-based traffic management system to overcome the problem of traffic control system in terms of flow and time management. The CCTV will be used as an input sensor that provides a real-time traffic data. Arduino board, Ethernet shield (Wiznet 5100) and LEDs (Light Emitting Diode) are used to setup the prototype system. It is use to demonstrate the T-junction added with green light delay interval time. The delay time will be programmed by using C++ programming language which will be compiled through Arduino IDE software. The Ethernet shield will act as the sender of the traffic data. The data will be transmitted to the server which will be done by CIDTS Unimas (Centre for Information Development and Services). Mobile application used by user will received the information provided by the server. The proposed project will improve the time management for road user to reach their destination. It can be further used on a larger scale in real time for better and safer road using Mobotix IP (Internet Protocol) camera that can analyse the traffic count automatically.